Electrical conduction of polyimide films prepared from polyamic acid (PAA) and pre-imidized polyimide (PI) solution (eXPRESS Polymer Letters, 2007)
Electrical conduction characteristics in two different polyimide films prepared by the imidization of polyamic acid (PAA) and pre-imidized polyimide (PI) solution were investigated. It is found that the current density of the polyimide film from PAA was higher than that of the polyimide film from PI at the same electric field, even though the conduction mechanism in both polyimide films follows the ionic hopping model. The hopping distance was calculated to be 2.8 nm for PAA type and 3.2 nm for PI type polyimide film. It is also found that the decay rate of the residual electrostatic charges on the polyimide films becomes faster in the PAA type than in the PI type polyimide film.